Determinan Faktor-faktor yang Berpengaruh terhadap Manajemen Laba - Ika Siti Fatimah; Destin Alfianika Maharani; Anastasia Anggarkusuma Arofah (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
Earnings management is an act of company managers to influence earnings in financial statements to achieve certain goals. Earnings management actions carried out by company managers will have an impact on the high and low profits presented in the financial statements. This study aims to empirically examine the effect of institutional ownership, profitability, firm size, and leverage on earnings management. The sampling method was used purposive sampling, there was 75 samples of manufacturing companies in the foods and beverages sector that meets the sample criteria with the 2019-2021 observation period. Data analysis technique using multiple linear regression analysis. The results of the study show that institutional ownership, profitability, firm size, and leverage simultaneously affect earnings management. Partialy profitability variable has a negative and significant effect on earnings management, while the variables of institutional ownership, firm size, and leverage have a negative and insignificant effect on earnings management.